Pediatric Hemophagocytic Lymphohistiocytosis: Formation of an Interdisciplinary HLH Working Group at a Single Institution. Issue 3 (13th April 2023) - Watts, Shelley; Diaz, Maranda; Teller, Christa; Hamby, Tyler; Guirola, Ricardo; Perez, Maria; Eames, Gretchen; Howrey, Richard; Rios, Ana; Trinkman, Heidi; Ray, Anish
Abstract : Fever of unknown origin is a common presentation in children with an extensive differential diagnosis that encompasses multiple specialties. From a hematologic standpoint, the differential includes hyperinflammatory syndrome, such as hemophagocytic lymphohistiocytosis (HLH), among others. Due to the rarity of HLH and nonspecific symptoms at initial presentation, specialists are often consulted later in the disease progression, which complicates disease evaluation further. Cook Children's Medical Center (CCMC) has recently developed a multidisciplinary histiocytic disorder group that is often consulted on cases presenting with fever of unknown origin to increase awareness and potentially not miss new HLH cases. In this study, we examine the clinical presentation and workup of 13 patients consulted by the HLH work group at a single institution and describe the clinical course of 2 patients diagnosed with HLH. The goal of this project was to describe the formation of a disease-specific team and the development of a stepwise diagnostic approach to HLH. A review of the current diagnostic criteria for HLH may be warranted given findings of markers such as soluble IL2 receptor and ferritin as nonspecific and spanning multiple disciplines including rheumatology, infectious disease, and hematology/oncology.